The Determinants of Online Impulsive Buying on Shopee: An Empirical Study - Anastasia, Nita; Widyaningtyas, Dian; Haryanto, Totok; Fauziridwan, Meydy (Jurnal Ekonomi dan Bisnis Digital, 2025)
This study aims to analyze the influence of sales promotion, hedonic shopping motivation, shopping lifestyle, and electronic word-of-mouth (E-WOM) on impulsive buying behavior. The research focuses on Shopee consumers in Purwokerto. The independent variables in this study are sales promotion, hedonic shopping motivation, shopping lifestyle, and E-WOM, while impulsive buying serves as the dependent variable. A quantitative research method was employed. The sample consisted of 119 respondents, selected using purposive sampling. Data were collected through a questionnaire utilizing a Likert scale. The collected data were analyzed using SPSS version 26. The results indicate that sales promotions, hedonic shopping motivation, and shopping lifestyle have a positive and significant effect on impulsive buying. However, E-WOM does not influence on impulsive buying.